1991
DOI: 10.1021/bi00223a007
|View full text |Cite
|
Sign up to set email alerts
|

Distal and proximal ligand interactions in heme proteins: correlations between carbon-oxygen and iron-carbon vibrational frequencies, oxygen-17 and carbon-13 nuclear magnetic resonance chemical shifts, and oxygen-17 nuclear quadrupole coupling constants in [C17O-] and [13CO]-labeled species

Abstract: We have obtained the oxygen-17 nuclear magnetic resonance (NMR) spectra of a variety of C17O-labeled heme proteins, including sperm whale (Physeter catodon) myoglobin, two synthetic sperm whale myoglobin mutants (His E7----Val E7; His E7----Phe E7), adult human hemoglobin, rabbit (Oryctolagus cuniculus) hemoglobin, horseradish (Cochlearia armoracia) peroxidase (E.C. 1.11.1.7) isoenzymes A and C, and Caldariomyces fumago chloroperoxidase (E.C. 1.11.1.10), in some cases as a function of pH, and have determined t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

26
204
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(230 citation statements)
references
References 95 publications
26
204
0
Order By: Relevance
“…Our Raman data, in which we find only a six-coordinate low spin form in the exogenous ligand-free ferrous preparation, is consistent with the observations of Dewilde et al 2 A confirmation of histidine as the proximal ligand is revealed by the analysis of the Fe 2ϩ CO complex. It is well known that there is an inverse correlation between the frequencies of the Fe-CO stretching modes and the frequencies of the C-O stretching modes of heme proteins and heme model compounds (17)(18)(19). As a result of this relation, which arises from the -electron back-donation from the d (dxz,dyz) orbitals of Fe to the empty * orbitals of CO, the bond order between iron and CO increases as the bond order between the carbon and oxygen atoms of CO decreases and vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…Our Raman data, in which we find only a six-coordinate low spin form in the exogenous ligand-free ferrous preparation, is consistent with the observations of Dewilde et al 2 A confirmation of histidine as the proximal ligand is revealed by the analysis of the Fe 2ϩ CO complex. It is well known that there is an inverse correlation between the frequencies of the Fe-CO stretching modes and the frequencies of the C-O stretching modes of heme proteins and heme model compounds (17)(18)(19). As a result of this relation, which arises from the -electron back-donation from the d (dxz,dyz) orbitals of Fe to the empty * orbitals of CO, the bond order between iron and CO increases as the bond order between the carbon and oxygen atoms of CO decreases and vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have inferred electrostatic potentials based on free energy measurements [e.g., pK a shifts of ionizable residues (9-11), reactivity differences among cysteines (12,13), equilibrium binding constants of charged ligands (14), and redox potential shifts (15)] or spectroscopic variations in probes incorporated into or bound to proteins [e.g., fluorescent dyes (16), 19 F and 13 C chemical shifts (17)(18)(19)(20)(21), and EPR-measured g-factor perturbations of nitroxides (22)]. These studies have spurred the ongoing development of electrostatic calculation methodology (6,7) and contributed greatly to our general recognition that the solvation environment within proteins is very different from water.…”
mentioning
confidence: 99%
“…These observations show that the specific DNA binding causes the structural change around the distal heme environment, which shifts the equilibrium between A 0 and A 3 conformers to the A 3 site and the narrowing of the A 0 mode. Although some controversy exists on the interpretation of the A 3 conformer of Mb (18,32,33), it is considered that a strong hydrogen bonding would increase the back-donation and enhance the Fe-C stretching frequency to ϳ520 cm Ϫ1 (35). A side chain of the replaced axial ligand is a possible candidate that exerts hydrogen-bonding interaction to the iron-bound CO.…”
mentioning
confidence: 99%